2022
DOI: 10.1146/annurev-control-042920-102205
|View full text |Cite
|
Sign up to set email alerts
|

Internal Models in Control, Bioengineering, and Neuroscience

Abstract: Internal models are nowadays customarily used in different domains of science and engineering to describe how living organisms or artificial computational units embed their acquired knowledge about recurring events taking place in the surrounding environment. This article reviews the internal model principle in control theory, bioengineering, and neuroscience, illustrating the fundamental concepts and theoretical developments of the few last decades of research. Expected final online publication date for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…However, a deep result from control theory, called the internal model principle (IMP) (see ref. 30 for a recent review), stipulates that every RPA network can, at least theoretically, be separated into two components - an internal model (IM) that dynamically evaluates the effect of disturbance by measuring the regulated output, and generates counteracting signals, that are then passed to the rest of the network (RoN) via the actuation mechanism to complete the feedback loop ( Fig. 2 A ).…”
mentioning
confidence: 99%
“…However, a deep result from control theory, called the internal model principle (IMP) (see ref. 30 for a recent review), stipulates that every RPA network can, at least theoretically, be separated into two components - an internal model (IM) that dynamically evaluates the effect of disturbance by measuring the regulated output, and generates counteracting signals, that are then passed to the rest of the network (RoN) via the actuation mechanism to complete the feedback loop ( Fig. 2 A ).…”
mentioning
confidence: 99%
“…Moreover, this structural characterisation would enable us to develop novel controller motifs that can potentially be synthetically engineered to correct for the failure of natural controllers. In this context, the Internal Model Principle (IMP) [12] from control theory provides a clue on how RPA systems may be organised. This principle asserts that for a system to be robust to a class of dynamic disturbances, it must contain a subsystem, called the internal model (IM), that is able to generate these disturbances, and then pass counteracting signals to the rest of the network (RoN) in a feedback fashion (see Figure 1).…”
Section: A the Formalism Of Reaction Networkmentioning
confidence: 99%
“…where f and g are nonlinear functions of the state variable x, and u is the disturbance input which enters linearly into the dynamics. For a recent review on IMP, we refer the readers to [12]. Generally, biomolecular networks exhibiting RPA are nonlinear and even the disturbances can enter their dynamics nonlinearly, typically via perturbations of the reaction propensities.…”
Section: A the Formalism Of Reaction Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…A normal form for output robustness based on internal model representation is proposed in [15]. A contemporary review of internal models can be found in [16].…”
Section: Introductionmentioning
confidence: 99%